Communication Network Analysis on the Issue of #PertaminaKembaliTerbakar on Social Media X year 2023 - Wangsa, Aurelia Kartika; Juliadi, Rismi; Astagini, Nuria (ARISTO, 2024)
The case of the Pertamina refinery that caught fire again in 2023 became a trending topic on social media platform X (formerly Twitter) shortly after the incident occurred. From this topic, researchers aimed to measure and analyze the communication network that was formed, the topics discussed, and the actors involved. Due to the limited research on social media communication networks related to the issue identification process for companies, this study also focused on analyzing the results of mapping the communication network that formed on social media platform X and its connection to the concept of reputation when a company faces a negative issue. Data collection was done using the Netlytic application, which was then processed using the Gephi application. From the data collection results, the research showed a diameter value of 9, indicating a relatively loose network of actors. The density, with a value of 0.001445, and the reciprocity, with a value of 0.0001443, indicated very low interaction density. From the actor's perspective, there were three main actors with the highest degree of centrality connecting other actors, but the topics discussed tended to be negative. These findings indicate that the actor @detikcom is dominant, with many other actors connected to the account to discuss topics related to Pertamina. The second dominant actors are @geiszchalifah and @giginpraginanto, who, upon further investigation, are active figures on social media providing information and commenting on political issues.